Alteration of POLDIP3 splicing associated with loss of function of TDP-43 in tissues affected with ALS. - Atsushi Shiga; Tomohiko Ishihara; Akinori Miyashita; Misaki Kuwabara; Taisuke Kato; Norihiro Watanabe; Akie Yamahira; Chigusa Kondo; Akio Yokoseki; Masuhiro Takahashi; Ryozo Kuwano; Akiyoshi Kakita; et al. (PLoS ONE, 2012)
Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disease caused by selective loss of motor neurons. In the ALS motor neurons, TAR DNA-binding protein of 43 kDa (TDP-43) is dislocated from the nucleus to cytoplasm and forms inclusions, suggesting that loss of a nuclear function of TDP-43 may underlie the pathogenesis of ALS. TDP-43 functions in RNA metabolism include regulation of transcription, mRNA stability, and alternative splicing of pre-mRNA. However, a function of TDP-43 in tissue affected with ALS has not been elucidated. We sought to identify the molecular indicators reflecting on a TDP-43 function. Using exon array analysis, we observed a remarkable alteration of splicing in the polymerase delta interacting protein 3 (POLDIP3) as a result of the depletion of TDP-43 expression in two types of cultured cells. In the cells treated with TDP-43 siRNA, wild-type POLDIP3 (variant-1) decreased and POLDIP3 lacking exon 3 (variant-2) increased. The RNA binding ability of TDP-43 was necessary for inclusion of POLDIP3 exon 3. Moreover, we found an increment of POLDIP3 variant-2 mRNA in motor cortex, spinal cord and spinal motor neurons collected by laser capture microdissection with ALS. Our results suggest a loss of TDP-43 function in tissues affected with ALS, supporting the hypothesis that a loss of function of TDP-43 underlies the pathogenesis of ALS.